Fighting Internet spam in Brazil - Historical overview and reflections on combating spam and managing port 25, coordinated by the Brazilian Internet Steering Committee - Hoepers, Cristine; Barbosa, Henrique Faulhaber; Steding-Jessen, Klaus (Comitê Gestor da Internet no Brasil, 2017)
153 p.